ANALISIS KEUNTUNGAN DAN HARAPAN KEUNTUNGAN CABAI MERAH PADA KLASTER CABAI DI KABUPATEN LAMPUNG SELATAN - Rachmat Kautshar Putra; Wan Abbas Zakaria; Eka Kasymir (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2017)
The study aimed to determine the profit of red chili farmings on cluster in South Lampung district and to find out the gain of scenario at that clusters.  It was conducted at clusters of red chili farming in South Lampung district.  Thirty six respondents were obtained by census method and be interviewed using questionnaires.  The analysis was performed using farm income, Bayes Theorem and profit expectation.  The results showed that red chili farming could give a favourable profit by looking at the R/C value which was more than one.  The red chili sales of scenario at the clusters in South Lampung district were determined based on the time and the price levels that occured in the first cropping pattern had the highest expectation occured on July (sales scenario of 25%) and August (sales scenario of 75%).  Meanwhile, the sales scenario for the second cropping pattern had the highest expectation occured on December (sales scenario of 25%) and on January (sales scenario of 75%). Key words : profit analysis, profit expectation, red chili farmings